The magellanic mollusca of Rochebrune and Mabille - Petit, Richard E. (Zootaxa, 2010)
The often confused authorship and date (1889) of Rochebrune & Mabille’s Mollusques portion of the Mission Scientifique du Cap Horn is explained. Other related papers of the 1880s by the same authors are examined and the Magellanic mollusks they named are listed with remarks on their current status. Comments in the literature about their work are quoted. The source of their material is explained.